Comparison between standard single chamber versus dual chamber low glucose degradation product peritoneal dialysis fluids. Issue 1 (30th July 2020) - Vareesangthip, Kornchanok; Vongsanim, Surachet; Fan, Stanley; Davenport, Andrew
Abstract: Dual chamber (DC) peritoneal dialysis (PD) dialysates contain fewer glucose degradation products (GDPs), so potentially reducing advanced glycosylation end products (AGEs), which have been reported to increase inflammation and cardiovascular risk. We wished to determine whether use of DC dialysates resulted in demonstrable patient benefits. Biochemical profiles, body composition, muscle strength, and skin autofluorescence measurements of tissue AGEs (SAF) were compared in patients using DC and standard single chamber dialysates. We studied 263 prevalent PD patients from 2 units, 62.4% male, mean age 61.8 ± 16.1 years, 78 (29.7%) used DC dialysates. DC patients were younger (55.9 ± 16.4 vs. 64.2 ± 15.4 years), and more had lower Davies comorbidity score (median 1 (0‐1) vs. 1 (0, 2)), slower peritoneal transport (D/P creatinine 0.67 ± 0.12 vs. 0.73 ± 0.13), greater extracellular water‐to‐total body water (ECW/TBW) ratio (0.46 ± 0.05 vs. 0.42 ± 0.06), all P < .001, whereas there were no differences in the duration of PD (median (IQR) 19 (8‐32) vs. 14 (8‐23) months), residual renal function (Kt/Vurea 0.71 ± 0.71 vs. 0.87 ± 0.82), urine volume (642 (175‐1200) vs. 648 (300‐1200) mL/day), hand grip strength (26.9 ± 10.5 vs. 24.9 ± 10.7 kg), C‐reactive protein (4(1‐10) vs. 4(2‐12) mg/L), and SAF (median 3.60 (3.02, 4.40) vs. 3.50 (3.00, 4.23)) AU. In our cross‐sectional observational study, we were not able to show a demonstrable advantage for using low GDP dialysates over conventional glucose dialysates, in terms of biochemical profiles, residual renal function, muscle strength, or tissue AGE deposition. More patients using low GDP dialysates were slower peritoneal transporters with higher ECW/TBW ratios.